ACROMEGALY AND TEETH - Mihaela Jana Tuculina; Ionela Teodora Dascălu; Oana Andreea Diaconu; Adina Turcu; Andreea Nicola; Sanda Mihaela Popescu; Cristian Petcu; Ruxandra Voinea Georgescu; Anda Dumitrascu; Mara Carsote (Romanian Society of Oral Rehabilitation, 2022)
Acromegaly, a GH (Growth Hormone) excess - related condition, has co-morbidities varying from cardio-metabolic events, sleep apnea, osteoporotic fractures, and oncologic risk especially of colonic cancer up to oral, facial and dental anomalies. We aim to briefly revise oro-dental status in acromegalic patients through a multidisciplinary perspective. This is a review of literature. Because of GH and IGF1 (Insulin-like Growth Factor) actions, a wide area of anomalies are registered, for example, mandibular protrusion, widening of maxillary, increased spaces between teeth, malocclusion, thick lips, all of them causing functional impairment and facial appearance changes. Oro-facial manifestations are among earliest signs; however, the acromegaly phenotype is recognizable after more than a decade of biochemical exposure to GH excess (unrecognized, untreated and/or uncontrolled acromegaly). The mentioned anomalies require a specialized team of medical dentists, and orthodontists, as well as otorhinolaryngology practitioners in addition to endocrinologists. Mandibular ramus has a larger height in acromegaly, main characteristic being increased L1/MP (labial inclination of mandibular central incisors) which might function as a discriminator parameter from non-acromegalic malocclusion. Some individuals might experience gingivitis, moderate chronic periodontitis or bulky oral bony outgrowths according to AcroDent study. Another consistent chapter of dental and periodontal complications is provided by the presence of secondary diabetes mellitus in acromegalic patients, a "sweet" complication that is controlled at the point when GH excess is controlled, due to hyperglycemic effect of GH and associated insulin resistance. An additional perspective on facial bones is related to GH excess - induced bone remodeling pattern that delays some dental procedures since acromegaly stabilization is mandatory first. Incrementally, the delay of dental intervention limits the dental management, finally requiring prosthetic approach. In the meantime, increased bone turnover associates anomalies of skeleton micro-architecture and increased osteoporotic fracture risk. High bone turnover should be taken into consideration when planning implant surgery. Awareness among dentists and orthodontists is essential to early recognition of acromegaly and its complications in order to improve the outcome. A close collaboration with endocrinologists is required.